WIMAX (International Journal of Engineering and Computer Science, 2014)
WIMAX stands for Worldwide Interoperability for Microwave Access. WiMAX refers to broadband wireless networks that are based on the IEEE 802.16 standard, which ensures compatibility and interoperability between broadband wireless access equipment .WiMAX, which will have a range of up to 31 miles, is primarily aimed at making broadband network access widely available without the expense of stringing wires (as in cable-access broadband) or the distance limitations of Digital Subscriber Line.